Obstetric Fistula in 2015 and Beyond - Arrowsmith, S (Nepal Journal of Obstetrics and Gynaecology, 2015)
Fistula effort was confined to a very few geographic areas, each of which were completely dominated by the spirit and energy of the founder of a fistula center. The list of leading surgeons contains names familiar to fewer and fewer active fistula care providers: Drs. Ann Ward, John Lawson, and Una Lister in Nigeria were all in the late prime of their lives; in the north of Nigeria, a leprosy surgeon was just getting started in fistula repair at a new center near Katsina: the founder being Dr. Kees Waaldiijk. In eastern Africa, Dr. Abbo Hassan Abbo was dominant in Sudan, the Hamlins in Ethiopia, and an odd band of travelling surgeons, including the late Dr. John Kelly, Dr. Brian Hancock, and Dr. Tom Raassen, were establishing themselves across the region. Also quite active, but completely unheralded were a cadre of non-Western surgeons just beginning long careers in fistula repair: Drs. Mulu Muleta and Ambaye w/ Michael in Ethiopia, Dr. Kalilou Ouattara in Mali, Dr. Serigne Gueye in Senegal, Dr. Khisa Wakasiaka in Kenya, Dr. Ojengbede Akanbi in Ibadan, Nigeria, and Dr. Jonathan Karshima in Jos. Meanwhile, Dr. Kundu Yangzom was quietly establishing a tradition of quality fistula care in Nepal.